Mechanisms of gas-coal thermal preparation in electromagnetic field - Starovoit, Anatoly; Chemerinskii, Michael; Malyi, Eugene (Publishing House of Lviv Polytechnic National University, 2014)
The article deals with the structure of lowmetamorphosed coal vitrain macromolecules. The mechanism of thermal preparation in gas coal electromagnetic field is shown. Розглянуто будову макромолекули вітрену малометаморфізованого вугілля. Наведено механізм термічної підготовки в електромагнітному полі газового вугілля.
Механізм термічної підготовки газового вугілля в електромагнітному полі
Keywords: macromolecule; chemical bonds; polarization; mechanism; hydrogenation; макромолекула; хімічні зв’язки; поляризація; механізм; гідрування